2019
DOI: 10.1038/s41467-019-08578-3
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and transcriptomic changes complement each other in the pathogenesis of sporadic Burkitt lymphoma

Abstract: Burkitt lymphoma (BL) is the most common B-cell lymphoma in children. Within the International Cancer Genome Consortium (ICGC), we performed whole genome and transcriptome sequencing of 39 sporadic BL. Here, we unravel interaction of structural, mutational, and transcriptional changes, which contribute to MYC oncogene dysregulation together with the pathognomonic IG- MYC translocation. Moreover, by mapping IGH translocation breakpoints, we provide evidence that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
124
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(135 citation statements)
references
References 81 publications
(104 reference statements)
6
124
0
5
Order By: Relevance
“…The germ line sequence of the patient is used, if available, to consider potential polymorphisms when assessing the identity of the rearranged sequence to the germ line. The read depth before and after the potential CSR identified is compared to determine the presence of isotype switching 26 . Besides, using both types of reads as well as paired reads aligning to different chromosomes, IgCaller identifies genome-wide rearrangements (deletions, inversions, gains and translocations) involving any of the Ig loci.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The germ line sequence of the patient is used, if available, to consider potential polymorphisms when assessing the identity of the rearranged sequence to the germ line. The read depth before and after the potential CSR identified is compared to determine the presence of isotype switching 26 . Besides, using both types of reads as well as paired reads aligning to different chromosomes, IgCaller identifies genome-wide rearrangements (deletions, inversions, gains and translocations) involving any of the Ig loci.…”
Section: Resultsmentioning
confidence: 99%
“…The third required piece of information is the BED files containing the genomic locations of the V and J genes of IGH/IGK/IGL (wgEncodeGencodeBasicV19 for hg19, and GencodeV29 for hg38), the CSR regions (Huebschmann et al, in preparation) 26 , and the sequences of the annotated D genes (extracted using the coordinates of the D genes reported in wgEncodeGencodeBasicV19 for hg19 and GencodeV29 for hg38). Although the user could define their own regions and sequences, these files are supplied within the IgCaller program both for hg19 and hg38.…”
Section: Methodsmentioning
confidence: 99%
“…Alignment of sequencing read pairs and variant calling were performed as recently described [66]. Briefly, reads were mapped to human reference genome (hg19) with bwa-mem (version 0.7.8, minimum base quality threshold set to zero [-T 0], remaining settings left to default) [67].…”
Section: Methodsmentioning
confidence: 99%
“…SNV and indels in matched tumor normal pairs were identified using the internal DKFZ variant calling workflows based on samtools/bcftools 0.1.19 with additional custom filters (optimized for somatic variant calling by deactivating the pval-threshold in bcftools) and Platypus 0.8.1, respectively, as described previously [66]. Gene annotation of variants was done with Annovar [68].…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Streich et al reported that MCL with blastoid and pleomorphic morphology frequently harbor both TP53 and CDKN2A/B aberrations, and that these cases are characterized by frequent chromothripsis [24]. Curiously, in sharp contrast to MCL, aberrations of TP53 and CDKN2A were mutually exclusive in Burkitt lymphoma and were very rarely observed in diffuse large B cell lymphoma [25][26][27]. In indolent lymphoproliferative malignancies, namely CLL and follicular lymphoma, deletions of CDKN2A are rare, and CDKN2A inactivation frequently correlates with the transformation to an aggressive lymphoma with adverse prognosis [28][29][30][31].…”
Section: Concurrent Aberration Of Tp53 and Deletion Of Cdkn2a Is Assomentioning
confidence: 99%